Fuzzy Control Chart For Analysis Of N-Policy FM/FM/1vacation Queueing System With Server Start-Up And Time-Out (Journal of Namibian Studies : History Politics Culture, 2023)
This paper we constructs the N-policy FM/FM/1 vacation queueing system  with server start-up and  time-out by using fuzzy control chart based on Zedeh extension law to transform fuzzy queues into family of crisp queues. Arrival rate, service rate and vacation times will all be made by fuzzy nature. We derive the membership functions of the parameters of the control chart corresponding to the expected system length L and also confirmed the parameters of the control chart for fuzzy. We have also set an numerical example.